New perspectives on DNA methylation modifications in ocular diseases - Fei-Fei Zong; Da-Dong Jia; Guang-Kun Huang; Meng Pan; Hao Hu; Shi-Yi Song; Liang Xiao; Ru-Weng Wang; Liang Liang (International Journal of Ophthalmology)
The methylation of DNA is a prevalent epigenetic modification that plays a crucial role in the pathological progression of ocular diseases. DNA methylation can regulate gene expression, thereby affecting cell function and signal transduction. Ophthalmic diseases are a kind of complex diseases, and their pathogenesis involves many factors such as genetic, environmental and individual differences. In addition, inflammation, oxidative stress and lipid metabolism, which abnormal DNA methylation is closely related to, are also considered to be major factors in eye diseases. The current understanding of DNA methylation in eye diseases is becoming more complex and comprehensive. In addition to the simple suppression of gene expression by hypermethylation, factors such as hypomethylation or demethylation, DNA methylation in non-promoter regions, interactions with other epigenetic modifications, and dynamic changes in DNA methylation must also be considered. Interestingly, although some genes are at abnormal methylation levels, their expression is not significantly changed, which indirectly reflects the complexity of gene regulation. This review aims to summarize and compare some relevant studies, and provide with new ideas and methods for the prevention and treatment of different eye diseases, such as glaucoma, retinoblastoma, and diabetic retinopathy.